2011
DOI: 10.1016/j.hrthm.2010.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic pattern of the intrinsic ganglionated nerve plexus in mouse heart

Abstract: Summary BACKGROUND Both normal and genetically modified mice are excellent models to investigate molecular mechanisms of arrhythmogenic cardiac diseases that may associate with an imbalance between the sympathetic and the parasympathetic nervous input to the heart. OBJECTIVE We sought to: (1) determine the structural organization of the mouse cardiac neural plexus; (2) identify extrinsic neural sources and their relationship with the cardiac plexus; and (3) reveal any anatomical differences in the cardiac p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
61
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 32 publications
9
61
0
3
Order By: Relevance
“…A similar location of cardiac ganglia was described by Maifrino et al [38]. In a study on mice, Rysevaite et al [56] also found the presence of ganglia spread in the immediate vicinity of the vena cava and the pulmonary veins. However, they found no ganglia around the coronary groove.…”
Section: Topography Of Cardiac Plexusessupporting
confidence: 79%
See 2 more Smart Citations
“…A similar location of cardiac ganglia was described by Maifrino et al [38]. In a study on mice, Rysevaite et al [56] also found the presence of ganglia spread in the immediate vicinity of the vena cava and the pulmonary veins. However, they found no ganglia around the coronary groove.…”
Section: Topography Of Cardiac Plexusessupporting
confidence: 79%
“…Since then, the problem has been studied and described for many amphibian, reptile, bird, and mammal species. Such strong interest in cardiac nerve structures is due to their important function: they regulate the function of the cardiac conduction system, the heart rhythm, and coronary circulation [56,65].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental and developmental studies of the autonomic cardiac nervous system have also been conducted in animals such as the mouse, rat, rabbit, chick, and dog (Armour et al, 1972;Benítez et al, 1959;Brack et al, 2011;Gomez, 1958;Haws and Burgess, 1978;Hildreth et al, 2008Hildreth et al, , 2009Kirby et al, 1980;Kuratani et al, 1991;Kuratani and Tanaka, 1990;Levy et al, 1966;Mabe and Hoover, 2011;Meyer et al, 2010;Mizeres, 1955Mizeres, , 1957Mizeres, , 1958Mizuno et al, 2010;Oliveira et al, 2010;Roberts, 1991;Schwartz, 2010;Scherlag et al, 2011;Shaner, 1930;Shoba and Tay, 2000;Uchida et al, 2010;Verberne et al, 1998). However, huge differences in the cardiac nervous system between humans and the experimental animals have been recognized (Batulevicius et al, 2003;Brugnaro et al, 2003;Kawashima, 2011;McKibben and Getty, 1968;Rysevaite et al, 2011;Pauza et al, 2002a,b). A through understanding of primate morphology is important because the primate ancestor diverged from the ancestor of the rodents, which includes the main experimental animals such as the rat, mouse, and rabbit.…”
Section: Introductionmentioning
confidence: 99%
“…A situação dos gânglios do plexo cardíaco de camundongos no tecido adiposo subepicárdico respeita o descrito para outros mamíferos, como o rato, o porco, o cão a ovelha e o homem (Davies et al, 1952;King e Coakley, 1958;Yuan et al, 1994;Armour et al, 1997, Hopkins, 2000Batulevicius et al, 2003, Saburkina, 2010Rysevaite et al, 2011). Na presente pesquisa foi possível detectar dois tipos Quando se avalia, na literatura, a disposição dos gânglios do plexo cardíaco, observa-se que uma série de trabalhos faz referência à sua distribuição sem, contudo, realizarem mensurações morfométricas (Pardini et al, 1987;Wallis et al, 1996;Singh et al, 1996;De Souza et al, 1996;Batulevicus et al,2003;Maifrino et al,2006;Gama et al,2010 (Wallis et al, 1996;Armour et al, 1997;Batulevicus et al, 2003;Jurgaitiené et al, 2004), enquanto que os pesquisadores que utilizaram contagem de preparados de membrana descrevem uma menor quantidade dessas células (De Souza et al, 1996 (NADH e AChE Histoquímica); Maifrino et al, 2006 (NADPH-diaphorase); Gama et al, 2010 (β-NADH diaphorase); Rysevaite et al, 2011 (Acetyltransferase -ChAT , 1997;Furlan et al, 1999;Miranda-Neto et al, 2000).…”
Section: Estereologia Número De Gânglios Cardíacosunclassified